2006
DOI: 10.4028/www.scientific.net/msf.514-516.1736
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Behaviour of a Glass Produced from a MSWI Bottom Ash

Abstract: This paper is mainly focused on the characterisation of a glass material (GM) obtained from the thermal treatment of a bottom ash (BA) produced at the Municipal Solid Waste (MSW) incineration plant of Valorsul. By melting the BA at 1400°C during 2 hours, and without using any chemical additives, a homogeneous black-coloured glass was obtained. The thermal and mechanical properties of this glass were characterised. The thermal expansion coefficient, measured by dilatometry, was 9-10 x 10-6 per °C and the modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…c) l(E)c50 based classification for waste (Wilke et al 2008; Pandard, Römbke 2013). d) Tua (acute toxic units) as an initial, background scoring value for indices or scales -for WW (HELCOM LAND 2007) and for waste (Lapa et al 2006). Tua based more sophisticated indices: avTx -average of toxicity index, i.e.…”
Section: Principles Of Aquatic Toxicity Classification Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…c) l(E)c50 based classification for waste (Wilke et al 2008; Pandard, Römbke 2013). d) Tua (acute toxic units) as an initial, background scoring value for indices or scales -for WW (HELCOM LAND 2007) and for waste (Lapa et al 2006). Tua based more sophisticated indices: avTx -average of toxicity index, i.e.…”
Section: Principles Of Aquatic Toxicity Classification Systemsmentioning
confidence: 99%
“…These values for industrial WW at the point of discharge toxicity to fish eggs were usually 2 (sometimes up to 6), umu-test 1.5-3, algae test 16, Daphnia 2-8, bacteria 4-32 at 10 (or 20) % effect (HELCOM MONAS 2011). e) Tua values based five toxicity classes were proposed for WW and natural waters (TB use of data) evaluation: a) no-acute toxicity (TU < 0.4); b) slight acute toxicity (0.4 < TU < 1.0); c) acute toxicity (1.0 < TU < 10); and, d) high acute toxicity (10 < TU > 100), very high acute toxicity (TU > 100), (Ronco et al 2005); more simple version was used for waste leachates (Lapa et al 2006 (Vindimian 2005). b) Integration of toxicity strength, persistence and specificity in trophic chain -Tp -toxic print is WW (effluent) characteristic; it is calculated by multiplying average toxicity AvTx and coefficient n (real number of tests which indicated (geno) toxic results).…”
Section: Principles Of Aquatic Toxicity Classification Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports show the possibility of slag and dust vitrification from an electric arc furnace with the addition of kaolin clay [52]. It has been found that the process of melting occurs at a temperature of about 1200ºC, and then after cooling the products were vitrified.…”
Section: Vitrification Of Wastementioning
confidence: 96%